2019
DOI: 10.4317/jced.55695
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endocan and vascular endothelial growth factor in recurrent minor aphthous ulcers

Abstract: Background: Recurrent aphthous ulcers (RAU) are common painful inflammatory lesions of the mucous lining of the mouth. Endocan, previously identified as endothelial cell specific molecule-1, is implicated as a vital player in the regulation of several inflammatory processes. A number of inflammatory cytokines and pro-angiogenic growth factors including VEGF upregulate endothelial cells synthesis and expression of endocan. Material and Methods: Clinical scores of pain and ulcer size as well as level of endocan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Endocan and VEGF values were found to be higher in patients with recurrent aphthous ulcers compared to controls. In the same study, it was emphasized that an increase in endocan was associated with an increase in pain score and vice versa 44 . It was reported that VEGF-A directly affects neurons, microglia, astrocytes, and Schwann cells, and has neurotrophic and neuroprotective activity in peripheral and central nervous systems 45 .…”
Section: Discussionmentioning
confidence: 90%
“…Endocan and VEGF values were found to be higher in patients with recurrent aphthous ulcers compared to controls. In the same study, it was emphasized that an increase in endocan was associated with an increase in pain score and vice versa 44 . It was reported that VEGF-A directly affects neurons, microglia, astrocytes, and Schwann cells, and has neurotrophic and neuroprotective activity in peripheral and central nervous systems 45 .…”
Section: Discussionmentioning
confidence: 90%